Enteral tube feeding and mortality in hospitalized older patients: A multicenter longitudinal study. Issue 5 (May 2020) - Veronese, Nicola; Cella, Alberto; Cruz-Jentoft, Alfonso J.; Polidori, Maria Cristina; Mattace-Raso, Francesco; Paccalin, Marc; Topinkova, Eva; Greco, Antonio; Mangoni, Arduino A.; Daragjati, Julia; Siri, Giacomo; Pilotto, Alberto; et al.
Summary: Background & aims: The literature regarding enteral nutrition and mortality in older frail people is limited and still conflicting. Moreover, the potential role of comprehensive geriatric assessment is poorly explored. We therefore aimed to investigate whether the Multidimensional Prognostic Index (MPI), an established tool that assesses measures of frailty and predicts mortality, may help physicians in identifying patients in whom ETF (enteral tube feeding) is effective in terms of reduced mortality. Methods: Observational, longitudinal, multicenter study with one year of follow-up. Data regarding ETF were recorded through medical records. A standardized comprehensive geriatric assessment was used to calculate the MPI. Participants were divided in low (MPI-1), moderate (MPI-2) or severe (MPI-3) risk of mortality. Data regarding mortality were recorded through administrative information. Results: 1064 patients were included, with 79 (13 in MPI 1–2 and 66 in MPI-3 class) receiving ETF. In multivariable analysis, patients receiving ETF experienced a higher risk of death (odds ratio, OR = 2.00; 95% confidence intervals, CI: 1.19–3.38). However, after stratifying for their MPI at admission, mortality was higher in MPI-3 class patients (OR = 2.03; 95%CI: 1.09–3.76), but not in MPI 1–2 class patients (OR = 1.51; 95%CI: 0.44–5.25). The use of propensity score confirmed these findings. Conclusions: ETF is associated with a higher risk of death. However, this is limited to more frail patients, suggesting the importance of the MPI in the prognostic evaluation of ETF.